2014
DOI: 10.5114/pdia.2014.40919
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selected ingredients of dietary supplements on skin condition

Abstract: Introduction and aim of the article. Healthy skin is an excellent barrier maintaining balance between the internal and external environment of the body. Because it is constantly changing as a result of, on the one hand, environmental factors and, on the other hand, the process associated with skin aging, it requires many nutrients and minerals that help maintain its homeostasis. The aim of this dissertation is to discuss the most commonly used ingredients in dietary supplements that improve the appearance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Moreover, Table 2 showed that high amount of hydroxyproline and total protein extracted from granulation tissue of healed excised wound at the end of the study indicate a better wound contraction due to the increase of collagen formation and increase the amount of protein by pomelo peel extract PPE treated groups which was significantly different from that of both diabetic control and normal control groups, these results were comparable to other previous studies for wound healing. 27,3132 (Erdinc K. et al 2010, Szyszkowska B et al 2014) in their study pomelo content of flavonoids, carotenoids and vitamin C, enhances the epithelial cells migration, proliferation and stimulate collagen synthesis. 3435 The increase in the hydroxyproline and total protein content are indicators of new tissues generation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Table 2 showed that high amount of hydroxyproline and total protein extracted from granulation tissue of healed excised wound at the end of the study indicate a better wound contraction due to the increase of collagen formation and increase the amount of protein by pomelo peel extract PPE treated groups which was significantly different from that of both diabetic control and normal control groups, these results were comparable to other previous studies for wound healing. 27,3132 (Erdinc K. et al 2010, Szyszkowska B et al 2014) in their study pomelo content of flavonoids, carotenoids and vitamin C, enhances the epithelial cells migration, proliferation and stimulate collagen synthesis. 3435 The increase in the hydroxyproline and total protein content are indicators of new tissues generation.…”
Section: Discussionmentioning
confidence: 98%
“…Androgens stimulate the production of sebum, growth of the sebaceous glands and hyperkeratinization. Recent studies have shown that diet could play a role in the pathogenesis of acne [ 3 , 4 ]. It has also been shown that a low glycemic index (GI) diet induced an improvement in acne severity and a parallel improvement in insulin sensitivity in young males with acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…It is of crutial importance to protect skin from negative factors like ultraviolet radiation, various chemicals, tobacco smoke, infections, as well as make available all the necessary nutrients in the diet, and appropriate care. In order to provide for normal functioning of the skin it is necessary to incorporate various foods of animal or plant origin, 18 which contain vitamins, minerals, proteins, essential fatty acids, [5][6][7][8][9][10][11][12][13][14][15][16][17] taking in consideration the type skin as well.…”
Section: Discussionmentioning
confidence: 99%